The Evolution and Distribution of Pneumococcal Serotypes in Adults Hospitalized With Community-Acquired Pneumonia in Spain Using a Serotype-Specific Urinary Antigen Detection Test: The CAPA Study, 2011–2018. (14th April 2021) - Torres, Antoni; Menéndez, Rosario; España, Pedro Pablo; Fernández-Villar, Jose Alberto; Marimón, José María; Cilloniz, Catia; Méndez, Raúl; Egurrola, Mikel; Botana-Rial, Maribel; Ercibengoa, María; Méndez, Cristina; Cifuentes, Isabel; et al.
Abstract: Background: Spain introduced the 13-valent pneumococcal conjugate vaccine (PCV13) in the childhood National Immunization Program in 2015–2016 with coverage of 3 doses of 94.8% in 2018. We assessed the evolution of all pneumococcal, PCV13 vaccine type (VT), and experimental PCV20-VT (PCV13 + serotypes 8, 10A, 11A, 12F, 15B, 22F, 33F) hospitalized community-acquired pneumonia (CAP) in adults in Spain from 2011–2018. Methods: A prospective observational study of immunocompetent adults (≥18 years) admitted to 4 Spanish hospitals with chest X-ray–confirmed CAP between November 2011 and November 2018. Microbiological confirmation was obtained using the Pfizer serotype-specific urinary antigen detection tests (UAD1/UAD2), BinaxNow test for urine, and conventional cultures of blood, pleural fluid, and high-quality sputum. Results: Of 3107 adults hospitalized with CAP, 1943 were ≥65 years. Underlying conditions were present in 87% (n = 2704) of the participants. Among all patients, 895 (28.8%) had pneumococcal CAP and 439 (14.1%) had PCV13-VT CAP, decreasing from 17.9% (n = 77) to 13.2% (n = 68) from 2011–2012 to 2017–2018 ( P  = .049). PCV20-VT CAP occurred in 243 (23.8%) of those included in 2016–2018. The most identified serotypes were 3 and 8. Serotype 3 accounted for 6.9% (n = 215) of CAP cases, remaining stable during the study period, and was associated with disease severity. Conclusions: PCV13-VT caused a substantial proportion of CAP in Spanish immunocompetent adults 8 years after introduction of childhood PCV13 immunization. Improving direct PCV13 coverage of targeted adult populations could further reduce PCV13-VT burden, a benefit that could be increased further if PCV20 is licensed and implemented. Abstract : Serotypes included in PCV13 caused 14% of hospitalized Community-Acquired Pneumonia (CAP) in immunocompetent adults in Spain 8 years after introduction of PCV13 childhood immunization. Direct vaccination with PCV13 currently and with extended spectrum vaccines in the future may help address CAP burden among adult populations.